The disruptive potential of DeFi - Robson, Karen, (SAGE business cases., 2022)
Decentralized finance (DeFi) is rapidly developing as an alternative to consumer reliance on large, centralized financial institutions to oversee and manage financial transactions. With the emergence of DeFi, transactions such as borrowing, lending, or currency exchanges, among others, could be completed entirely without the need for traditional financial services firms. As the sector emerges, it brings the potential to disrupt the finance industry as we know it. However, the future of DeFi remains highly uncertain and full of risk.